Adaptive and innovative students' metacognition in solving logarithm tasks. Issue 1 (February 2021) - Imama, M; Siswono, T Y E; Ismail
Abstract: Problem solving as approach in teaching and learning has important position to face students' future. Students' problem-solving skill and knowledge depend on several aspects, one of which is metacognition. Metacognition is the awareness of students in using their minds to plan, monitor, and evaluate the cognitive processes and strategies used. Students have different cognitive styles, including adaptive and innovative style. The selection of participants in this qualitative study used a cognitive style questionnaire to find students who had cognitive styles of adaptation and innovation. Data collection using task-based interviews about algorithms. Analysis of research results from the 10th grade students as participants used steps that are data reduction, data presentation, and verification, as well as checking data validity. The results showed that adaptive student at planning stage to understand the problem through reading effort, solve the logarithm problem using her knowledge directly, and plan to check the calculation, writing, and methods used. In monitoring stage, she did not estimate time consuming for solving problem. Student have not been confident yet that her plan was correct. She thinks that she has forgotten, although using methods for checking of solution was correct. Finally, at evaluation stage, adaptive students have no other way to understand problem, believes that his knowledge could help to solving problems, look back the plan that has been used, and she has no other way to re-examine his work. The innovative student has several similar stages with the adaptive student. She has estimated time consuming for solving logarithm problem and check calculation results, writing, and methods used. She has been confident using his method to understand problem, and check his work twice until it was correct. He has alternative strategy although the alternative is more complicated so it is not used.